Classical mechanics - Goldstein, Herbert; Poole, Charles; Safko, John (New Delhi: Pearson Education, 2000)
Classical Mechanics has been the standard in advanced classical mechanics courses for thirty years. It emphasizes formulations important for the study of modern physics which prepare students to apply the principles and mathematical techniques of classical mechanics in later study. By deepening and building student understanding of classical mechanics, the text helps students make the connections between classical and modern physics.
Appendix A-B, 601-638p.; Bibliography 617-622p.; Index 625-638p.
Keywords: Mechanics; Physics